2017
DOI: 10.1002/ijc.30730
|View full text |Cite
|
Sign up to set email alerts
|

Discs large homolog 5 decreases formation and function of invadopodia in human hepatocellular carcinoma via Girdin and Tks5

Abstract: Invadopodium formation is a crucial early event of invasion and metastasis of hepatocellular carcinoma (HCC). However, the molecular mechanisms underlying regulation of invadopodia remain elusive. This study aimed to investigate the potential role of discs large homolog 5 (Dlg5) in invadopodium formation and function in HCC. We found that Dlg5 expression was significantly lower in human HCC tissues and cell lines than adjacent nontumor tissues and liver cells. Lower Dlg5 expression was associated with advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 39 publications
(83 reference statements)
2
35
0
Order By: Relevance
“…Overexpression of DLG5 inhibited glioma cells malignant biological behaviors of glioblastoma cells. Similar results were reported in many human cancers, such as bladder cancer, prostate cancer, breast cancer, and hepatocellular carcinoma 19,20,58 . We also found that knockdown of RAX2 could increase DLG5 expression.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Overexpression of DLG5 inhibited glioma cells malignant biological behaviors of glioblastoma cells. Similar results were reported in many human cancers, such as bladder cancer, prostate cancer, breast cancer, and hepatocellular carcinoma 19,20,58 . We also found that knockdown of RAX2 could increase DLG5 expression.…”
Section: Discussionsupporting
confidence: 87%
“…DLG5 belongs to the membrane associated guanylate kinase (MAGUK) family, participates in epithelial cell polarity maintenance and cancer development 18 . DLG5 expression was downregulated in many human cancers, such as bladder cancer, prostate cancer, breast cancer, and hepatocellular carcinoma, not only that, knockdown of DLG5 significantly increased cell migration and invasion in these cancers 19,20 .…”
Section: Introductionmentioning
confidence: 98%
“…SH3PXD2A-AS1 is an antisense transcript transcribed from SH3PXD2A and located on chromosome 10 with 2023 bp length. And SH3PXD2A has been identified to exert oncogenic roles in multiple cancers [31-34]. In this study, we found that dysregulation of SH3PXD2A-AS1 is correlated with clinicopathological factors in CRC patients.…”
Section: Introductionmentioning
confidence: 57%
“…DLG5 is a cell polarity gene and its downregulation has been implicated in the malignancy of breast , prostate (Tomiyama et al, 2015) and bladder cancers (Zhou et al, 2015). It has been recently found that lower DLG5 expression is correlated with advanced stages of HCC and essential for invadopodium formation, an event critical to cancer metastasis (Ke et al, 2017). It is surprising that our study has identified a stage-III specific upregulation in DLG5.…”
Section: Discussionmentioning
confidence: 50%